Judicial Pardon of Punishment: An Evaluative and Comparative Review - Mohamed, Gehad; Qudah, Mouaid Al (International Journal of Membrane Science and Technology, 2023)
Unlike other laws, under the UAE Code of crimes and punishments No. (31) of 2021, the concept of judicial pardon of punishment refers to the legal authority vested in a judicial system to grant forgiveness or leniency to individuals who have been found guilty of a crime. Judicial pardon serves as a mechanism for eliminating the prescribed penalties for certain offenses. Comparative analysis reveals that the granting of a judicial pardon is typically based on a range of factors, such as the nature of the offense, the severity of the punishment, the individual’s behavior, the presence of extenuating circumstances, and considerations of justice and fairness. It allows the judicial system to exercise discretion and flexibility in recognizing cases where the application of the prescribed punishment may be deemed unnecessary or where rehabilitation and reintegration into society have been successfully demonstrated. The decision to grant or deny a pardon rests within the discretion of the judiciary, considering the best interests of society, the rights of victims, and the individual’s potential for reform. Thus, pardoning punishment can have significant implications for the convicted individual, as it offers the opportunity for a fresh start and a second chance at rebuilding their life. Yet, the analysis indicates that there is room for improving the legal structure of judicial pardon under the UAE Law and points out towards some possible deeper structure reforms.